Transformasi lanskap perairan di Kawasan Percandian Muarajambi dalam memori kolektif masyarakat lokal - Ari Mukti Wardoyo Adi; Nainunis Aulia Izza; Muhammad Rohiq; Dwi Rahariyoso (Berkala Arkeologi, 2022)
The Muarajambi Temple Complex is a Buddhist Cultural Conservation area in Sumatra, located in 3,981 hectares fluvial landform. This area is frequently flooded, both during the rainy season and the high tides, but local people are still living in this area. This paper discusses the research on the waterscape transformation in the Muarajambi Temple Complex based on collective memory and the related physical evidence. The research method used is the comparison of satellite images using GIS software and the confirmation of the results by the local people through interviews. The research results indicate that, unlike the previous interpretation, the water network had not been an all-time active transportation infrastructure. In addition, the research identified numerous ancient hydrological landforms in the area.